Одинокая волчица, или Я проткну твое сердце шпилькой: [роман] / Юлия Шилова - Шилова Юлия Витальевна (АСТ, 2014)
Экземпляры: ф.17 (20200316) / Инвентарный номер: 51948 / Цена: 50.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Ш 59 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-44